2020
DOI: 10.1002/cam4.3568
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world experience of carfilzomib‐associated cardiovascular adverse events: SEER‐Medicare data set analysis

Abstract: Carfilzomib was approved for the treatment of multiple myeloma in 2012 and since then there have been concerns for cardiovascular toxicity from its use. With this study, we aim to further study the hazards and underlying risk factors for cardiovascular adverse events associated with carfilzomib. This study was conducted using Surveillance, Epidemiology, and End Results (SEER)‐Medicare data set of multiple myeloma from 2001 to 2015. Data were analyzed for hazards ratio of cardiovascular adverse events between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 23 publications
3
27
0
1
Order By: Relevance
“…All proteasome inhibitors have been associated with multiple cardiovascular complications including hypertension, congestive heart failure and arrhythmias, though the association is strongest with carfilzomib. 6466 In a phase 3 study comparing carfilzomib to bortezomib in 929 patients with multiple myeloma, 15% of patients on carfilzomib developed grade 3 or 4 hypertension while only 3% on bortezomib did. 67 Other studies have provided consistent estimates.…”
Section: Overview Of Hypertension With Anti-cancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…All proteasome inhibitors have been associated with multiple cardiovascular complications including hypertension, congestive heart failure and arrhythmias, though the association is strongest with carfilzomib. 6466 In a phase 3 study comparing carfilzomib to bortezomib in 929 patients with multiple myeloma, 15% of patients on carfilzomib developed grade 3 or 4 hypertension while only 3% on bortezomib did. 67 Other studies have provided consistent estimates.…”
Section: Overview Of Hypertension With Anti-cancer Agentsmentioning
confidence: 99%
“…67 Other studies have provided consistent estimates. 64,66,68 For example, a large meta-analysis of 24 prospective trials, including 2594 patients, found that 12.2% of patients on carfilzomib developed hypertension. 69 The hypertension associated with carfilzomib may be dose dependent.…”
Section: Overview Of Hypertension With Anti-cancer Agentsmentioning
confidence: 99%
“…Both bortezomib and carfilzomib carry distinct, but not insignificant side-effect profiles, the former being associated with peripheral neuropathy while the latter, based on the myeloma literature, carries a theoretical risk of cardiotoxicity ( 140 , 142 ). The magnitude of risk in heart transplant candidates is unknown and must be balanced with the potential benefits given the ultimate goal.…”
Section: Current Approaches To Desensitization In Heart Transplantationmentioning
confidence: 99%
“…Частота специфических для карфилзомиба неже лательных явлений (≥III степени тяжести) на фоне терапии Kd70 была невысока и для сердечной недо статочности составила 2,9 %, для артериальной ги пертензии -6,0 % и для ишемической болезни сер дца -0,84 % [16]. Согласно данным американского эпидемиологического регистра SEER риск сердечно сосудистых осложнений увеличивают возраст стар ше 75 лет, предшествующая патология сердца и со судов, ожирение и режим введения карфилзомиба 2 раза в неделю по сравнению с введением 1 раз в неделю [18].…”
Section: противомиеломные препараты продемонстрировавшие активность при двой ной рефрактерности карфилзомиб / дексаметазонunclassified